Theranostic applications of selenium nanomedicines against lung cancer - Shaowei Liu; Weifeng Wei; Jinlin Wang; Tianfeng Chen (Journal of Nanobiotechnology, 2023)
Abstract The incidence and mortality rates of lung cancer are among the highest in the world. Traditional treatment methods include surgery, chemotherapy, and radiotherapy. Although rapid progress has been achieved in the past decade, treatment limitations remain. It is therefore imperative to identify safer and more effective therapeutic methods, and research is currently being conducted to identify more efficient and less harmful drugs. In recent years, the discovery of antitumor drugs based on the essential trace element selenium (Se) has provided good prospects for lung cancer treatments. In particular, compared to inorganic Se (Inorg-Se) and organic Se (Org-Se), Se nanomedicine (Se nanoparticles; SeNPs) shows much higher bioavailability and antioxidant activity and lower toxicity. SeNPs can also be used as a drug delivery carrier to better regulate protein and DNA biosynthesis and protein kinase C activity, thus playing a role in inhibiting cancer cell proliferation. SeNPs can also effectively activate antigen-presenting cells to stimulate cell immunity, exert regulatory effects on innate and regulatory immunity, and enhance lung cancer immunotherapy. This review summarizes the application of Se-based species and materials in lung cancer diagnosis, including fluorescence, MR, CT, photoacoustic imaging and other diagnostic methods, as well as treatments, including direct killing, radiosensitization, chemotherapeutic sensitization, photothermodynamics, and enhanced immunotherapy. In addition, the application prospects and challenges of Se-based drugs in lung cancer are examined, as well as their forecasted future clinical applications and sustainable development. Graphical Abstract